Investigation the Use of Smartphone by Babol Dental students in 2023 - Arezou Forootan; Reza Ghorbanipour; Seyed Ali Seyed Majidi (آموزش پزشکی)
Background and Objective: Considering the advancements in technology and the increasing use of smartphones in society, this study aimed to investigate the extent of smartphone usage by dental students at Babol University of Medical Sciences in 2023. Methods: In this descriptive-analytical study, 183 dental students from Babol University of Medical Sciences participated. The data collection tool included a questionnaire examining various aspects of smartphone usage. The extent of smartphone utilization for general use, educational purposes, and students' attitudes towards using smartphones for educational goals was analyzed based on gender and educational level using SPSS software version 26 and independent samples T-test at a significance level of 0.05. Findings: All participants had access to the internet and smartphones. 53% of students used educational applications. The most common location for using smartphones for educational purposes was at home or in dormitories. The social media platforms primarily used for educational purposes included Telegram and YouTube. The overall attitude of students towards the use of smartphones in the learning process was positive, with no significant differences in attitudes observed between genders or across different educational levels. Conclusion: This research indicates that students effectively use smartphones for educational purposes, and digital tools have become an integral part of modern education.